Enhancing Functional Recovery Through Intralesional Application of Extracellular Vesicles in a Rat Model of Traumatic Spinal Cord Injury - Romanelli, Pasquale; Bieler, Lara; Heimel, Patrick; Škokić, Siniša; Jakubecova, Dominika; Kreutzer, Christina; Zaunmair, Pia; Smolčić, Tomislav; Benedetti, Bruno; Rohde, Eva; Gimona, Mario; Hercher, David; et al. (Frontiers in Cellular Neuroscience, 2022)
Local inflammation plays a pivotal role in the process of secondary damage after spinal cord injury. We recently reported that acute intravenous application of extracellular vesicles (EVs) secreted by human umbilical cord mesenchymal stromal cells dampen the induction of inflammatory processes following traumatic spinal cord injury. However, systemic application of EVs is associated with delayed delivery to the site of injury and the necessity for high doses to reach therapeutic levels locally. To resolve these two constraints, we injected EVs directly at the lesion site acutely after spinal cord injury. We report here that intralesional application of EVs resulted in a more robust improvement of motor recovery, assessed with the BBB score and sub-score, as compared to the intravenous delivery. Moreover, intralesional application was more potent in reducing inflammation and scarring after spinal cord injury than intravenous administration. Hence, development of EV-based therapy for spinal cord injury should aim at an early application of vesicles close to the lesion.